KORELASI PROGRAM PENGELOLAAN PENYAKIT KRONIS BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN TERHADAP KUALITAS HIDUP PASIEN di UNEJ MEDICAL CENTER - Ida Srisurani Wiji Astuti; Adhang Isdyarsa; Cicih Komariah (Jurnal Ilmu Kesehatan Masyarakat, 2018)
Prolanis BPJS (the program of Chronic Disease Management by Social Security Health Agency) was launched for financing efficiency for chronic disease in Indonesia. The efficiency has made a noticeable impact.This study aims to observe the correlation between the program and the increase of patients’ quality of life as a result of the implementation of Prolanis BPJS. The research deployed cross sectional analytic approach in which data was collected in January 2017.During the research, 2 (two) types of questionnaire such as questionnaire of service quality based on the SERVQUAL (Service Quality) and the SF-36 questionnaire related to the quality of life were distributed. A total of 22 respondents were involved through total sampling method to identify both the value of perception and expectations of each respondent towards the quality of primary health care facilities in Unej Medical Center. Spearman method was implemented for data analysis reportingthe findings that in general the quality of service provided by PROLANIS BPJS indicated no correlation with the patients’ quality of life at UMC (p) 0,072,and (r) 0,391. Eight dimensions of life quality were examined, and only two of them were showed correlation with the quality of service provided, namely: the dimensions of physical function and bodily pain